Perancangan Aplikasi Penjualan Furniture Berbasis Android : (Studi Kasus Masnur Joglo) - Astin Rambu Guna; Rambu Yetty Kalaway; Raynesta Mikaela Indri Malo (Router : Jurnal Teknik Informatika dan Terapan, 2024)
Furniture has high added value and significant global competitiveness, largely due to the diversity of natural raw materials available in Indonesia, such as wood, rattan, and bamboo, as well as distinctive and high-quality designs. This advantage is supported by the skills and competence of the available human resources, making Indonesian furniture superior to products from other countries. Product quality is a key element in winning market competition, as it impacts customer satisfaction and loyalty. Masnur Joglo, a furniture company located on Jl. Muara Karya, specializes in producing various types of furniture from high-quality woods such as super mahogany and red teak. However, the purchasing system, which requires customers to visit the store directly and manually record prices, results in inefficiencies in terms of time and transportation costs. Customers often need to visit multiple stores to find the desired product, which is an inefficient process. To address these challenges, this study proposes the development of an Android-based sales application as a solution. This application is designed to expand Masnur Joglo's market reach and facilitate online ordering of furniture products, anytime and anywhere. The study aims to design and develop an Android-based sales information system that can enhance operational efficiency and streamline the sales process while better meeting customer needs. The application development method employs the waterfall model and uses MySQL and Firebase databases.